2021
DOI: 10.1007/s13314-021-00433-z
|View full text |Cite
|
Sign up to set email alerts
|

First report of Neoscytalidium novaehollandiae on common sage (Salvia officinalis)

Abstract: In June 2020, many plants exhibited symptoms of root rot and foliar blight in the experimental field of common sage in Şanlıurfa province, Turkey. The pathogen was identified as Neoscytalidium novaehollandiae based on morphological characteristics and phylogenetic analysis of partial sequence of the transcription elongation factor 1-α gene and the internal transcribed spacer of rDNA. Koch's postulates were fulfilled by successful re-isolation of the pathogen from inoculated plants in the pathogenicity assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…N. novaehollandiae was reported in four provinces of Iran including Sistan and Baluchestan, Kermanshah, Gilan and Kerman on mulberry ( Morus alba ), black hawthorn ( Crataegus pentagyna ), hornbeam ( Carpinus betulus ), beech ( Fagus orientalis ), and oak ( Quercus brantii ) 36 – 38 . Furthermore, the pathogenicity of this species was confirmed on plants in China, Turkey and Australia which infected baobab ( Adansonia gibbosa ), bardi bush ( Acacia synchronica ), blue grevillea ( Grevillia agrifolia ), rattlepod ( Crotalaria medicaginea ) 39 , mango ( Mangifera indica ) 40 , 41 , elm ( Ulmus densa ) 42 , Grapevine ( Vitis vinifera ) 43 , pistachio ( Pistacia vera ) 44 , almond ( Prunus dulcis ) 45 , japanese persimmon ( Diospyros kaki ) 46 , tomato ( Solanum lycopersicum ( 47 , pear ( Pyrus communis ) 48 and sage ( Salvia officinalis ) 49 . Based on the results, the host range of N. novaehollandiae was confined to 12 species of the plant hosts and most of them were woody plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. novaehollandiae was reported in four provinces of Iran including Sistan and Baluchestan, Kermanshah, Gilan and Kerman on mulberry ( Morus alba ), black hawthorn ( Crataegus pentagyna ), hornbeam ( Carpinus betulus ), beech ( Fagus orientalis ), and oak ( Quercus brantii ) 36 – 38 . Furthermore, the pathogenicity of this species was confirmed on plants in China, Turkey and Australia which infected baobab ( Adansonia gibbosa ), bardi bush ( Acacia synchronica ), blue grevillea ( Grevillia agrifolia ), rattlepod ( Crotalaria medicaginea ) 39 , mango ( Mangifera indica ) 40 , 41 , elm ( Ulmus densa ) 42 , Grapevine ( Vitis vinifera ) 43 , pistachio ( Pistacia vera ) 44 , almond ( Prunus dulcis ) 45 , japanese persimmon ( Diospyros kaki ) 46 , tomato ( Solanum lycopersicum ( 47 , pear ( Pyrus communis ) 48 and sage ( Salvia officinalis ) 49 . Based on the results, the host range of N. novaehollandiae was confined to 12 species of the plant hosts and most of them were woody plants.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity tests on branches of selected forest trees (12–15 years old) showed that lesion lengths varied between species including Punica granatum, Alnus glutinosa, Pterocarya fraxinifolia, Parrotia persica, Mespilus germanica and Quercus castaneifolia 38 . Furthermore, other studies briefly described the pathogenicity of N. novaehollandiae on Morus alba , Crataegus pentagyna , Carpinus betulus , Fagus orientalis , Quercus brantii , Adansonia gibbosa , Acacia synchronica , Grevillia agrifolia , Crotalaria medicaginea , Mangifera indica, Ulmus densa , Vitis vinifera , Pistacia vera , Prunus dulcis , Diospyros kaki , Solanum lycopersicum, Pyrus communis , and Salvia officinalis 36 – 42 , 44 – 49 .…”
Section: Discussionmentioning
confidence: 99%
“…(Hajlaoui et al., 2018 ; Nouri et al., 2018 ; Oksal et al., 2020 ; Ören et al., 2020b , 2022b ), Pyrus communis (Oksal and Özer, 2021 ), Quercus spp. (Sabernasab et al., 2019 ), Salix alba (Türkölmez et al., 2019b ), Salvia officinalis (Derviş et al., 2021 ), Solanum lycopersicum (Türkölmez et al., 2019c ; Derviş et al., 2020b ), Solanum tuberosum (Derviş et al., 2020a ) and Vitis vinifera (Rolshausen et al., 2013 ; Correia et al., 2016 ; Akgül et al., 2019 ; Oksal et al., 2019 ; Arkam et al., 2021 ; Moghadam et al., 2022 ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…Elif) plants grown in commercial fields of Koruklu village, Akc ßatepe district of S ßanlıurfa Province, T € urkiye, were affected by N. dimidiatum (as N. novaehollandiae). Leaf chlorosis and blight, defoliation and root rot were some of the symptoms caused by the pathogen prior to plant death (Dervis ß et al, 2021).…”
Section: Impactsmentioning
confidence: 99%
“…In recent years, N. novaehollandiae , described by Palvic et al [ 5 ], has been reported as one of the most important species from various hosts, such as mango ( Mangifera indica ) [ 6 ], Persian oak ( Quercus brantii ) [ 7 ], pistachio ( Pistacia vera ) [ 8 ], grapes ( Vitis vinifera ) [ 9 ], tomato ( Solanum lycopersicum ) [ 10 ], Japanese persimmon ( Diospyros kaki ) [ 11 ], almonds ( Prunus dulcis ) [ 12 , 13 ], pears ( Pyrus communis ) [ 14 ], sage ( Salvia officinalis ) [ 15 ], mulberry ( Morus alba ) [ 5 ], cherry tree ( Prunus avium ) [ 16 ], plum ( Prunus domestica ) [ 17 ], and pine ( Pinus eldarica ) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%